The Role of Innovative Products in Creating Competitive Advantages in the Food Supplements Market: The Experience of Herbamama LLC - Vladimir Kochney (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
— Food supplements market competition requires companies to depend on innovation for maintaining their competitive edge. This research assesses how innovative products increase Herbamama LLC's competitive edge in its industry-leading position. The study applies econometric analysis to existing financial and operational company records to evaluate how innovation affects Herbamama LLC along with marketing intensity, customer engagement and geographical extent on competitive supremacy. R&D investments combined with new product introductions emerged as the leading element in building competitive advantage according to the research findings. Customer interaction together with marketing activities enhances competitive position substantially but product quality together with market conditions has an indirect impact. The study demonstrates that businesses must combine innovative practices with strategic marketing and customer interaction tactics to preserve their market position. Organizations operating in the food supplement industry will find useful knowledge through this study which also sets the stage for further research focusing on how competitive advantage unfolds within other niche markets